Determining of optimum irrigation schedules for drip irrigated Shiraz vineyards in the Breede River Valley - Lategan, Eugene Lourens (Stellenbosch : Stellenbosch University, 2011)
Thesis (MScAgric)--Stellenbosch University, 2011.